Sunrise on the reaping - Collins, Suzanne; White, Jefferson (New York City : Scholastic Audio Books, 2025)
The phenomenal fifth book in the Hunger Games series! Acclaimed actor Jefferson White, who starred in Paramount Network's Yellowstone as Jimmy Hurdstrom, brings his talent to the worldwide best-selling Hunger Games series as narrator of the Sunrise on the Reaping audiobook! When you've been set up to lose everything you love, what is there left to fight for? As the day dawns on the fiftieth annual Hunger Games, fear grips the districts of Panem. This year, in honor of the Quarter Quell, twice as many tributes will be taken from their homes. Back in District 12, Haymitch Abernathy is trying not to think too hard about his chances. All he cares about is making it through the day and being with the girl he loves. When Haymitch's name is called, he can feel all his dreams break. He's torn from his family and his love, shuttled to the Capitol with the three other District 12 tributes: a young friend who's nearly a sister to him, a compulsive oddsmaker, and the most stuck-up girl in town. As the Games begin, Haymitch understands he's been set up to fail. But there's something in him that wants to fight . . . and have that fight reverberate far beyond the deadly arena.
Unabridged.
Narrator: Jefferson White.
Requires the Sora app or a modern web browser.
Keywords: Young Adult Fiction; Science Fiction & Fantasy; Young Adult Literature; Electronic books